Quality of family planning services delivery and family planning client satisfaction at health facilities in Nepal: Further analysis of the 2015 Nepal Health Facility Survey: DHS further analysis report No. 113 - Pant,Prakash Dev (2018)
ABSTRACT: The quality of family planning (FP) services at the health facility and client satisfaction among those served on the day of the survey in Nepal were examined using the Nepal Health Facility Survey 2015 data. The analysis was guided by the structure (staff, guidelines, equipment, medicine, and commodities), process (provider's adherence to the provision of quality FP service) and outcome (client's overall satisfaction with services) framework suggested by Donabedian (1988). The results showed that about 98% of the health facilities in Nepal are providing at least one FP method in most health facilities for six or more days per week. The service readiness status of the health facility did not appear to be a significant influencer in determining the quality of FP services or FP client satisfaction. The provider's adherence to the provision of quality FP services did not show differences by most characteristics of clients, providers, and facilities in this study. Clients who were counseled on a FP method, when compared with those not counseled, were more likely to receive quality FP service. Similarly, services received from a provider with the opportunity of promotion were more likely to receive quality FP services. Clients who lived in the hills ecological region were less likely to be satisfied than those living in mountainous regions. Although 88.5% of clients were satisfied with the FP service they received in the health facility, higher client satisfaction was observed among those who received services from a provider with their job description; those receiving FP services at primary health care centers (PHCCs), health posts (HPs), and urban health centers (UHCs); and those receiving services from a facility with electricity. Clients living in the hills, when compared with mountains, and those living in Province 2 compared with Province 1, were less likely to be satisfied. This indicates that improving the skills of providers, ensuring job descriptions for all providers, improving the FP service delivery system in the facility, and having electricity in the facility all lead to improved client satisfaction. Because improved service readiness did not appear as an influencing factor in process as well as outcome measures, there is a clear need to improve the lacking or poor components of FP service readiness at all facility levels. KEYWORDS: Adherence to provision of quality FP service, client satisfaction, family planning health facilities, infection control, NHFS, quality of care, SARA